Who am I?. (2nd August 2022) - Demetriadi, Nicola
Abstract : How do I view myself in my role when working with children? As a profession, the early years sector has never faced such pressures. External factors impact on our professional identity, and now, more than ever before, how we are viewed by society, politicians and policy makers, matters.